Hubungan Fungsi Kognitif dengan Kualitas Hidup Pada Lansia di Panti Wreda Wilayah Kota Surakarta - Wahyu Aprilia Ningrum; Adisty Rose Artistin (Malahayati Nursing Journal, 2023)
ABSTRACT Elderly are people over 60 years of age. As people get older, humans will experience a degenerative aging process which will have an impact on changes in humans, not only physical changes, but also cognitive, emotional, and social. In the aging process there are many health problems in the elderly, one of which is experiencing changes in cognitive function, changes in cognitive function in the elderly are associated significantly with an increase in depression, stress, and have an impact on quality of life. This study aims to determine the relationship between cognitive function and quality of life in the elderly at Nursing Homes in the Surakarta City Region, namely at the Aisyiyah Sumber Solo Nursing Home and the Dharma Bhakti Nursing Home. This type of research uses a quantitative method with a descriptive analytic research method through a cross sectional approach. The number of samples in this study were 39 respondents who included the inclusion criteria of 35 respondents. The sampling technique used in this study is Non-Probability Sampling with total sampling. This study used the MMSE questionnaire instrument for cognitive function and WHOQoL-BREF to determine quality of life. Univariate analysis used descriptive statistics and bivariate analysis used the chi-square test. Based on the results of this study, it shows that there is a significant relationship between cognitive function and quality of life in the elderly, the p value is (0.001) where the significant value is less than (0.05). Thus it can be concluded that there is a relationship between cognitive function and quality of life in the elderly at the Surakarta City Region Nursing Home. Keywords: Elderly, Cognitive Function, Quality of Life   ABSTRAK Lansia adalah orang yang berusia di atas 60 tahun. Semakin bertambahnya usia, manusia akan mengalami proses penuaan secara degeneratif yang akan berdampak pada perubahan-perubahan pada diri manusia, tidak hanya perubahan fisik, tetapi juga kognitif, perasaan, dan sosial. Pada proses menua ada banyak permasalahan kesehatan pada lansia salah satunya yaitu mengalami perubahan fungsi kognitif, perubahan fungsi kognitif pada lansia berasosiasi secara signifikan dengan peningkatan depresi, stress, dan memiliki dampak terhadap kualitas hidup. Penelitian ini bertujuan untuk mengetahui hubungan fungsi kognitif dengan kualitas hidup pada lansia di Panti Wreda Wilayah Kota Surakarta yaitu di Panti Jompo Aisyiyah Sumber Solo dan Panti Wreda Dharma Bhakti. Jenis penelitian ini menggunakan metode kuantitatif dengan metode penelitian deskriptif analitik melalui pendekatan cross sectional. Jumlah sampel dalam penelitian ini adalah 39 responden yang termasuk kriteria inklusi sebanyak 35 responden. Teknik sampling yang digunakan dalam penelitian ini adalah Non Probability Sampling dengan jenis total sampling. Penelitian ini menggunakan instrument kuesioner MMSE untuk fungsi kognitif dan WHOQoL-BREF mengetahui kualitas hidup. Analisa univariat menggunakan statistic deskriptif dan Analisa bivariat menggunakan uji chi-square. Berdasarkan hasil penelitian ini menunjukan bahwa ada hubungan yang signifikan antara fungsi kognitif dengan kualitas hidup pada lansia didapatkan p value sebesar (0.001) dimana nilai significant tersebut kurang dari (0.05). Demikian dapat di simpulkan adanya hubungan fungsi kognitif dengan kualitas hidup pada lansia di Panti Wreda Wilayah Kota Surakarta. Kata Kunci: Lansia, Fungsi Kognitif, Kualitas Hidup